(Supplementary Table 1) 230Th/U results for stalagmite Cuba Grande (CG) from Pinar del Rio, supplementary data to: Fensterer, Claudia; Scholz, Denis; Hoffmann, Dirk; Mangini, Augusto; Pajon, Jesus M (2010): 230Th/U-dating of a late Holocene low uranium speleothem from Cuba. IOP Conference Series: Earth and Environmental Science, 9(1), 012015 - Fensterer, Claudia; Scholz, Denis; Hoffmann, Dirk (PANGAEA - Data Publisher for Earth & Environmental Science, 2010)
We present 22 U-series ages for a stalagmite from north-western Cuba based on multi-collector inductively coupled plasma mass spectrometry (MC-ICPMS) and thermal ionisation mass spectrometry (TIMS). Our results reveal that the stalagmite continuously grew within the last ~1400a. Low uranium content of the sample and thus, extremely low 230Th concentrations limit the precision and accuracy of 230Th/U-dating by TIMS. Samples measured by MC-ICPMS show a high variability of 232Th content along the growth axis with some sections significantly affected by initial 230Th from a detrital phase. An a-priori bulk earth ratio for (238U/232Th) cannot be used to accurately account for this initial 230Th. Using an age model based on the 230Th/U ages determined on samples with low or negligible 232Th concentration, we find that the (238U/232Th) activity ratio of the detrital phase is an order of magnitude larger than the bulk earth value, indicating the importance of an accurately determined correction factor.
This dataset is supplement to doi:10.1088/1755-1315/9/1/012015
Keywords: Datensammlung